More than our pain : affect and emotion in the era of Black Lives Matter - Hinderliter, Beth, 1973-; Peraza, Steve (State University of New York Press, 2021)
"Covering rage and grief, as well as joy and fatigue, examines how Black Lives Matter activists, and the artists inspired by them, have mobilized for social justice"-- Provided by publisher.
Keywords: Black lives matter movement.; African Americans -- Psychology.; Affect (Psychology) -- Social aspects -- United States.; Affect (Psychology) -- Political aspects -- United States.; Emotions -- Social aspects -- United States.; Emotions -- Political aspects -- United States.; African Americans -- Social conditions -- 1975-; United States -- Race relations -- Psychological aspects.; Minorities -- Study and teaching.; Social sciences.; Electronic books.; Mouvement Black Lives Matter.; Noirs américains -- Psychologie.; Noirs américains -- Conditions sociales -- 1975-; États-Unis -- Relations raciales -- Aspect psychologique.; Minorités -- Étude et enseignement.; Sciences sociales.; Livres numériques.; ethnic studies.; social sciences.; e-books.; SOCIAL SCIENCE / Ethnic Studies / African American Studies.; African Americans -- Psychology; African Americans -- Social conditions; Black lives matter movement; Emotions -- Political aspects; Emotions -- Social aspects; Race relations -- Psychological aspects; United States; Since 1975